Financial Analysis Training Enhances Students' Professional Competencies - Yenny Wati; Yusrizal Yusrizal; Suyono Suyono (Plakat : Jurnal Pelayanan Kepada Masyarakat, 2023)
This community service activity was implemented due to a lack of understanding of financial analysis supplied by vocational high schools. This activity is designed to help students improve their critical thinking, analytical skills, and professional abilities. Methods such as instructions and practical training in financial analysis, discussion methods, and questionnaire distribution are used to ensure that this community service activity remains effective in subsequent years. This action will be carried out offline on Thursday, April 6, 2023. This activity drew 45 participants, all of whom were in grade 11 and majoring in accounting at Metta Maitreya vocational high school. According to the evaluation results, students' understanding of financial analysis increased by 71% during the training. This increase was due to students discussing material during the training process, which was more of a two-way interaction, resulting in a more interesting and quality learning experience. This financial analysis training is regarded as beneficial and has a positive impact on Metta Maitreya vocational high school students. This training is designed to excite students' enthusiasm for accounting topics, particularly financial statement analysis.